2016
DOI: 10.1039/c6sm01072e
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of binary colloidal monolayers

Abstract: Experiments and simulations are used to study the kinetics of crystal growth in a mixture of magnetic and nonmagnetic particles suspended in ferrofluid. The growth process is quantified using both a bond order parameter and a mean domain size parameter. The largest single crystals obtained in experiments consist of approximately 1000 particles and form if the area fraction is held between 65-70 % and the field strength is kept in the range of 8.5-10.5 Oe. Simulations indicate that much larger single crystals c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…A custom code was written in MATLAB (Mathworks c , Version 2014, Natick, MA) for image processing and centroid identification of particles in every frame. The details of this procedure can be found in a prior study [56].…”
Section: Experiments Methodsmentioning
confidence: 99%
“…A custom code was written in MATLAB (Mathworks c , Version 2014, Natick, MA) for image processing and centroid identification of particles in every frame. The details of this procedure can be found in a prior study [56].…”
Section: Experiments Methodsmentioning
confidence: 99%
“…In atomic crystals, engineering structural defects is an experimental challenge for two reasons [10]: first, current visualization techniques at the atomic scale do not provide a high spatial or time resolution [11,12]; second, no current technique can control the density of defects in a systematic manner [13]. The first challenge can be overcome studying colloidal crystals as models for atomic systems [14,15], where colloidal particles can be individually tracked using standard digital video microscopy techniques [16][17][18]. Here, we demonstrate that the second challenge can be solved combining a binary colloidal mixture and an optical random potential generated by a speckle light pattern.…”
mentioning
confidence: 99%
“…Similar to one-component hard spheres, they are also the simplest multicomponent colloidal system and thus, form a reference model to study phase transitions of mixtures 5,12,14,15 . Crystals of these systems were observed by Sanders and Murray back in 1978, whilst analysing the microscopic structure of gem opals, which are composed of silica colloids and had an structure analogue to AlB 2 and NaZn 13 18 . So far, both experimental and simulation studies have identified that the phase diversity found in binary mixtures depends on the size ratio of the components, the number ratio and total concentration of the particles 5,6,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have identified the face-centered cubic (fcc) -often in a random mixture with hexagonal close packing (hcp)-, as the solid stable structure 5,12 . Crystallisation of multicomponent colloidal mixtures has acquired more interest, as these present a richer and more complex phase behaviour than their monocomponent counterpart 5,[12][13][14][15][16][17] . Amongst these systems, we find binary mixtures of hard spheres, which are composed of two populations of spheres of differing sizes.…”
Section: Introductionmentioning
confidence: 99%